Exploring users' experiences of accessing out-of-hours primary medical care services. Issue 6 (30th November 2007) - Richards, S H; Pound, P; Dickens, A; Greco, M; Campbell, J L
Abstract : Background: Since 2000, out-of-hours primary medical care services in the UK have undergone major changes in the organisation and delivery of services in response to recommendations by the Carson Review and more recently, through the new General Medical Services Contract (GMS2). People calling their general practice in the evening or at weekends are redirected to the out-of-hours service which may offer telephone advice, a home visit or a visit to a treatment centre. Little is known about users' experiences under the new arrangements. Aim: To explore users' experiences of out-of-hours primary medical care. Design of study: A qualitative study employing focus groups and telephone interviews. Setting: Three out-of-hours primary medical care service providers in England. Methods: Focus groups and telephone interviews were conducted with 27 recent users of out-of-hours services. Results: Key areas of concern included the urgency with which cases are handled, and delays when waiting for a call back or home visit. Users felt that providers were reluctant to do home visits. The service was regarded as under-resourced and frequently misused. Many expressed anxiety about calling, feeling unsure about how appropriate their call was and many were uncertain about how the service operated. Conclusions: Service users need clear information on how current out-of-hours services operate and how it should be used. Problems with triaging need to be addressed, users should be kept informed of any delays, and care needs to be taken to ensure that the new arrangements do not alienate older people or individuals with complex health needs.